Improving The Effectiveness Of Performance Management System Through Adkar-Based Change Management Analysis: A Case Study Of PT Transportasi Angkutan Darat (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to evaluate the effectiveness of change management in the Key Performance Indicator (KPI) Planning process at PT Transportasi Angkutan Darat (TAD) using the ADKAR framework. The main problems identified include insufficiently challenging KPI targets, insufficiently specific indicators, and suboptimal cascading processes. A mixed methods approach was used, combining quantitative survey data from managerial-level employees at the head office of PT TAD and in-depth interviews to gain a more comprehensive understanding. The results indicate that the Desire and Ability dimensions are in the strong category, driven by managerial motivation and established operational routines. However, the Awareness, Knowledge, and Reinforcement dimensions are at a lower level of effectiveness due to a lack of clarity regarding the reasons for KPI changes, inconsistencies in knowledge transfer during role transitions, and the absence of a structured feedback mechanism. Based on these findings, this study proposes improvement strategies through strengthening leadership-led communication, systematic integration of knowledge transfer into the managerial work cycle, and institutionalization of performance feedback into evaluation routines. Theoretically, this study contributes to the development of change management literature by demonstrating the application of ADKAR in diagnosing performance management system challenges in the context of a large transportation services company in the railway sector. Practically, the research results provide guidance for strengthening the KPI Planning process to make it more consistent, measurable, and aligned with the organization's strategic objectives.